Regulation of cellular sterol homeostasis by the oxygen responsive noncoding RNA lincNORS - Wu, Xue; Niculite, Cristina M.; Preda, Mihai Bogdan; Rossi, Annalisa; Tebaldi, Toma; Butoi, Elena; White, Mattie K.; Tudoran, Oana M.; Petrusca, Daniela N.; Jannasch, Amber S.; Bone, William P.; Zong, Xingyue; et al. (Nature communications, 2020)
We hereby provide the initial portrait of lincNORS , a spliced lincRNA generated by the MIR193BHG locus, entirely distinct from the previously described miR-193b-365a tandem. While inducible by low O 2 in a variety of cells and associated with hypoxia in vivo, our studies show that lincNORS is subject to multiple regulatory inputs, including estrogen signals. Biochemically, this lincRNA fine-tunes cellular sterol/steroid biosynthesis by repressing the expression of multiple pathway components. Mechanistically, the function of lincNORS requires the presence of RALY, an RNA-binding protein recently found to be implicated in cholesterol homeostasis. We also noticed the proximity between this locus and naturally occurring genetic variations highly significant for sterol/steroid-related phenotypes, in particular the age of sexual maturation. An integrative analysis of these variants provided a more formal link between these phenotypes and lincNORS , further strengthening the case for its biological relevance. Noncoding transcripts contribute to the adaptation of cellular processes to oxygen levels. Here the authors characterize a hypoxia responsive lncRNA lincNORS and show that it has a role in cellular sterol homeostasis.